Comparison of Perceptions and Smoking Cessation Experiences Between Smokers With and Without Serious Mental Illness in a Large Health Maintenance Organization. Issue 4 (2nd October 2021) - Kertes, Jennifer; Neumark, Yehuda; Grunhaus, Leon; Stein-Reisner, Orit
Abstract: Objective: Smoking prevalence is threefold higher among people with serious mental illness (PWSMI) than in the general population, yet smoking cessation rates for PWSMI are lower. Numerous reasons have been posited as to why tobacco use is higher and abstinence rates are lower among PWSMI. This study explores smoking cessation perceptions and experiences among PWSMI and people without serious mental illness (SMI). Methods: Participants in this cross-sectional study were recruited from among members of a large health maintenance organization (HMO) in Israel who had registered for or commenced a smoking cessation program in 2015 through 2017. The sample comprised 208 PWSMI and a matched sample of people without SMI ( N = 428). Telephone surveys were used to collect information about smoking status and smoking/cessation history, use of smoking cessation programs and aids (prescription medications, nicotine replacement therapy, electronic cigarettes), motivation and intention to quit, self-efficacy (to quit), smoking cessation outcome expectancies, physician support to quit, barriers and facilitators for those who had not quit, and reinforcements/challenges for those who had quit. Results: Of those without SMI, 27% quit smoking compared to 20% of PWSMI ( p = .051). Irrespective of mental health status, the most significant predictor of abstinence was the use of smoking cessation prescription medications. Family physicians were significantly less likely to inquire about motivation to quit, refer to smoking cessation programs, or prescribe smoking cessation medications for PWSMI than for people without SMI. Beyond these factors, no differences were noted between respondents with and without SMI regarding motivation to quit, intention to quit, and abstinence self-efficacy. PWSMI who had not quit were more likely to be concerned about how quitting might affect their functioning and how they would pass the time without cigarettes. Conclusions: PWSMI have similar levels of motivation and intention to quit smoking as those without SMI. However, they are disadvantaged by the reduced support received from their family physicians and lower cessation medication usage. Efforts to promote the implementation of smoking cessation treatment guidelines will help promote smoking abstinence among PWSMI.